Strategi Bisnis Pt Xyz Guna Meningkatkan Daya Saing Pada Industri Almunium - Wemby Gustiar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Competitive ability has become very important for a company. This happens because with a good competing ability that is able to make a company a leader in the market. Competitive ability or competitiveness can be formed if the company has the right strategies executed. The purpose of this study is to: 1) know the internal state of PT XYZ seen from the strengths and weaknesses owned by PT XYZ, 2) know the external state of PT XYZ seen from the strengths and weaknesses owned by PT XYZ, 3) exactly which can be recommended to PT XYZ to improve competitiveness. Quantitative Strategic Planning Matrix (QSPM) analysis is used to determine the best strategy. This study found that many competitors make distributors and consumers have many choices. The main strategy derived from the analysis is the market development strategy. By opening new branches in different places with different geography with the intention of acquiring a new market.